Section the Library and Information Sciences at the International Scientiﬁc and Practical Symposium REGIONAL COMPETITIVENESS BASED ON THE RESEARCH, INNOVATION AND TECHNOLOGY TRANSFER, Colloquia Professorum “Tradition and Innovation in Scientiﬁc Research”, (Confluenţe Bibliologice, 2016)
Press Release on section: Library and Information Sciences within the International Scientiﬁc and Practical Symposium REGIONAL COMPETITIVENESS BASED ON THE RESEARCH, INNOVATION AND TECHNOLOGY TRANSFER, Colloquia Professorum “Tradition and Innovation in Scientiﬁc Research”, VI-th edition, dedicated to Professor Nicolae Filip’s Year.
Keywords: Library and Information Sciences; Colloquia Professorum; Nicolae Filip (1926-2009)